Identification of Seven Aberrantly Methylated and Expressed Genes in Adrenocortical Carcinoma - Xiao, He; He, Weixiang; Chen, Ping; Xu, Deqiang; Zeng, Guang; Li, Zhuo; Huang, Mingliu; Wang, Xinghuan; DiSanto, Michael E.; Zhang, Xinhua (Frontiers in Endocrinology, 2019)
Background: Adrenocortical carcinoma (ACC) is a rare endocrine malignancy with an unfavorable prognosis and limited treatment options. Nevertheless, no clinically applicable molecular markers have been identified for the progression of ACCs. DNA methylation alterations were found to contribute to the development of ACC in recent decades. Material and Methods: The aims of the current study was to identify the abnormally methylated differentially expressed genes (DEGs) in ACCs, and to elucidate the mechanistic basis for these changes. Analyses were conducted on gene expression and gene methylation profile datasets to identify the aberrantly methylated DEGs. The DAVID software was used to conduct the analyses of functional enrichment on screened genes. Finally, expression was validated, and the relationship between abnormally methylated DEGs and clinical features was determined via the Oncomine database and The Cancer Genome Atlas (TCGA). To further verify the altered expression and methylation status of our identified genes we also validated these changes at the tissue and cellular levels. Results: We screened and identified 92 differentially expressed genes and 802 abnormally methylated genes. Furthermore, 7 aberrantly methylated and dysregulated genes were identified and validated, along with a number of functional enriched pathways. Among these 7 genes, the expression or methylation status is significantly correlated with different pathological stages and overall rates of survival. In validation, the expression of 7 genes were significantly altered and 5 genes were hypermethylated in ACC. Conclusions: Our study identified abnormally methylated DEGs and potentially affected pathways in ACCs, from which we could begin to understand the basic molecular mechanisms of these alterations. Moreover, these abnormally methylated genes might serve as therapeutic targets and biomarkers to allow ACC patients to be more precisely diagnosed and effectively treated.